Sugars as complementary alternative food for the establishment of Nesidiocoris tenuis in greenhouse tomato - Urbaneja-Bernat, Pablo; Mollá-Hernández, Óscar; Alonso, M.; Bolckmans, Karel; Urbaneja, Alberto; Tena, Alejandro (2017)
Nesidiocoris tenuis (Reuter) (Hemiptera: Miridae) is an omnivorous generalist predator which is augmentatively released and conserved for control of whiteflies (Hemiptera: Aleyrodidae) and Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in tomato crops. Eggs of Ephestia kuehniella Zeller (Lepidoptera: Pyralidae) are often provided as factitious prey to improve the establishment of N.tenuis after its release. We first tested different amounts of E.kuehniella eggs per plant to optimize N.tenuis establishment and then investigated whether the amount of eggs that optimized N.tenuis establishment might be reduced by adding sugars (hydrocapsules filled with 0.5m sucrose) under walk-in cage and commercial greenhouse conditions. These experiments demonstrated that the addition of sugar to the diet of N.tenuis could half the amount of E.kuehniella eggs required to establish N.tenuis. Under greenhouse conditions, the progeny of N.tenuis per plant did not differ significantly between E.kuehniella alone or the half amount of E.kuehniella plus hydrocapsules. These results demonstrated that the sugar could partially substitute for E.kuehniella eggs improve establishment of N.tenuis and suggest that natural sugars such as nectar and honeydew might also beneficial.